Dinamika Yayasan Pulih Aceh dalam Memutus Rantai Kekerasan Terhadap Perempuan dan Anak yang Terjadi di Aceh (Studi Dinamika Organisasi) - Elisa Dwi Suci (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2022)
Abstract Pulih Aceh Foundation is an organization that handles psychosocial and mental problems for survivors (victims of difficult events) through advocacyactivities. In this case, the researcher wants to reveal the dynamics that occur inthe Pulih Aceh Foundation in carrying out advocacy both internally andexternally. This study uses modern organizational theory according to AmitaiEtzioni in 1985. This study uses qualitative research methods with data collectiontechniques carried out through interviews, observations, and documentation. Theresults showed that there were several dynamics that occurred in the PulihFoundation when carrying out advocacy activities to break the chain of violencethat occurred in Aceh, namely, the lack of internal coordination of the management, miscommunication between the community and the management,unable to implement the program due to the refusal of the donors of the PulihAceh Foundation. However, from the dynamics faced by the Pulih Foundation,several potentials can be obtained, namely, forming cooperation, facilitatingwork, creating complex interactions, existing among the community.Keywords: Dynamics, Recovery, Survivors, Aceh Recovery Foundation.